Pushing daisies. The complete first season [videorecording (DVD)] - Pace, Lee, 1979-; Friel, Anna, 1976-; McBride, Chi; Dale, Jim; Greene, Ellen; Kurtz, Swoosie; Chenoweth, Kristin (Warner Home Video, 2008)
Ned can bring the dead to life briefly when he touches them, and must touch them again to reverse the spell. Along with a private eye, he uses his gift to help solve crimes and collect the rewards.